2019
DOI: 10.3899/jrheum.181438
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies in Patients with Antineutrophil Cytoplasmic Antibody-associated Vasculitis: A Population-based Cohort Study

Abstract: Objective Patients with ANCA-associated vasculitides (AAV) exhibit higher rates of malignancy than the general population. We assessed whether the cancer risk is increased in a well-characterized population-based cohort of AAV in southern Sweden, followed for a median time of 8 years. Methods With case record review, the outcomes and malignancy development in a cohort of 195 patients with AAV [granulomatosis with polyangiitis (GPA), microscopic polyangiitis, and eosinophilic GPA] diagnosed between 1997 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…Lower SIRs than previously were reported when follow-up data from the European Vasculitis Study Group clinical trial were analyzed and compared with previous studies, which was contributed to lower total exposure to cyclophosphamide. Presently, a persistent increased risk of overall malignancy, bladder cancer, and pancreatic cancer, as well as a markedly increased risk of squamous cutaneous skin cancer (SCC), was confirmed [28]. On a positive note, there was no increase in the incidence of cancers other than SCC for those treated with <10 g cyclophosphamide, which is a reference standard for the total cyclophosphamide exposure when used for inductive immunosuppressive treatment in AAV, including in our hospital.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Lower SIRs than previously were reported when follow-up data from the European Vasculitis Study Group clinical trial were analyzed and compared with previous studies, which was contributed to lower total exposure to cyclophosphamide. Presently, a persistent increased risk of overall malignancy, bladder cancer, and pancreatic cancer, as well as a markedly increased risk of squamous cutaneous skin cancer (SCC), was confirmed [28]. On a positive note, there was no increase in the incidence of cancers other than SCC for those treated with <10 g cyclophosphamide, which is a reference standard for the total cyclophosphamide exposure when used for inductive immunosuppressive treatment in AAV, including in our hospital.…”
Section: Discussionmentioning
confidence: 55%
“…The authors emphasize though that diagnosis based on needle biopsy may not be sufficient and these two diagnoses might coexist. Conversely, there is an extensive number of malignancy studies during AAV follow-up [24][25][26][27][28]. The course of the disease with frequent relapses can be a challenge as lung tumors can be difficult to distinguish from pulmonary AAV activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pankhurst et al reported that AAV increased the risk of concurrent or preceding malignancy [17]. The increased risk of malignancy in patients with AAV has been largely attributed to the carcinogenic effects of cyclophosphamide [18]. Some pathogenic mechanisms have been postulated to explain the association between vasculitis and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the standard treatment is a combination of corticosteroids with cyclophosphamide in the induction period, followed by lower doses of corticosteroids in combination with azathioprine or methotrexate in the maintenance period (14). However, a population-based cohort study of 195 patients observed a persistent increased risk for overall malignancies after the usage of cyclophosphamide (19). Clinical trials and observational studies have reached an agreement that glucocorticoids are a fundamental drug for the standard induction therapies in patients with GPA (20).…”
Section: Discussionmentioning
confidence: 99%